TEACHERS' BELIEFS ON MULTIPLE INTELLIGENCE BASED ENGLISH TEACHING FOR YOUNG LEARNERS - Ririn Tutik Faidah; Endang Fauziati; Suparno Suparno (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
Multiple intelligences theory asserted that human intelligence is not only measured by standardized IQ test on verbal and mathematical ability. However, this theory assumed that human intelligences contains of nine types of intelligences showed by each individual. By recognizing the different type of intelligences, it will help to know the different style of learners. Starting from this point, many teachers who understand the differences in learning among the students, they started to implement this theory for their instruction in order to improve the quality of teaching. This study was aimed to explore the teachers’ beliefs about the use of multiple intelligences based English teaching for young learners. The researcher used descriptive qualitative design to explore the teachers’ beliefs on the use of multiple-intelligences based English teaching for EFL young learners. This study was conducted in one of the elementary schools in Surakarta, which implemented multiple intelligences theory as a system in their instruction process. Two teachers were chosen to participate in this study and data was collected through the interview. The finding revealed that teachers’ beliefs on multiple intelligences theory based English teaching for young learners are a best strategy to be implemented in current teaching and learning process at their school. They believed that multiple intelligences system enhance the students’ achievement. They also realized the importance of the multiple intelligences theory based English teaching to improve their instruction.